2014
DOI: 10.1177/1045389x14549873
|View full text |Cite
|
Sign up to set email alerts
|

Validation and evaluation of damage identification using probability-based diagnostic imaging on a stiffened composite panel

Abstract: Probability-based diagnostic imaging, as one of the damage identification methods using ultrasonic guided waves, has been attracting increasing attention by researchers in the community of structural health monitoring. However, the probability-based diagnostic imaging algorithm’s influencing parameters, including the selection of certain damage index and frequency, the network of sensing paths, and the size of the effective elliptical distribution area, are empirically determined. This experience dependency li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 35 publications
0
51
0
Order By: Relevance
“…The usual transducer network configuration employed to identify damage with the RAPID algorithm consists of the transducer network located around the damage (see [2][3][4]). This study aims at damage identification in any part of the structure with a transducer network regularly distributed on the structure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The usual transducer network configuration employed to identify damage with the RAPID algorithm consists of the transducer network located around the damage (see [2][3][4]). This study aims at damage identification in any part of the structure with a transducer network regularly distributed on the structure.…”
Section: Methodsmentioning
confidence: 99%
“…Zhao et al [2] detected and localized rivet cracks and corrosion on an aircraft aluminum wing, Wu et al [3] used the RAPID with a composite panel with bonded T-stringers, combining several frequencies for an improved damage assessment, and Wang et al [4] identified a through-thickness hole in a composite stiffened panel.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao [6] compared the theoretical resolutions in a reconstruction image with that of circular, square, and parallel linear PZT sensor arrays. Wu [16] placed PZT sensors in a square pattern on a stiffened composite panel, and compared the performance with related sensing paths enclosed in a circle and square area. Dziendzikowski [17] defined a signature function for an inhomogeneous noncircular PZT sensor array to normalize the intensity map in a reconstruction image.…”
Section: Introductionmentioning
confidence: 99%
“…e anisotropy of the aircra pallet will be highlighted by the complex structure and structural characteristic changes, which makes it di cult to accurately obtain the Lamb wave velocity. e probability-based diagnostic imaging method is a fast and simple damage imaging method that does not use the Lamb wave velocity [3,52]. e damage index of each path in the pitch-catch sensor network is used in this method.…”
Section: Introductionmentioning
confidence: 99%